Toxic Effects of Lantana camara Crude Extracts on Spodoptera litura (Fabr.) - Pung, T.; Srimongkolchai, W. (Asian Journal of Chemistry, 2011)
Lantana camara flowers were extracted by Soxhlet apparatus for 8 h with n-hexane, dichloromethane and methanol, successively. Each crude extract of flowers was tested for topical toxicity by applying the extract on the third thorax of Spodoptera litura (second instar). Results showed that the 10 % (w/v) of dichloromethane crude extract was the most effective, causing 56 % of S. litura to die in 7 days. The 10 % of n-hexane extract caused 34 % death, which was higher than the 2 % death observed in controls (p < 0.05). The mean lethal concentration (LC50) of the dichloromethane extract toward S. litura larvae was 9.453 % w/v. The dichloromethane and n-hexane crude extracts reduced feeding of the third instar of S. litura. There were no differences in larvae mortality among the three extracts when given orally. However, these experiments terminated at 7 days, so longer term effects remain to be studied.